2020
DOI: 10.1038/s41467-020-19890-8
|View full text |Cite
|
Sign up to set email alerts
|

RNA-mediated control of cell shape modulates antibiotic resistance in Vibrio cholerae

Abstract: Vibrio cholerae, the cause of cholera disease, exhibits a characteristic curved rod morphology, which promotes infectivity and motility in dense hydrogels. Periplasmic protein CrvA determines cell curvature in V. cholerae, yet the regulatory factors controlling CrvA are unknown. Here, we discover the VadR small RNA (sRNA) as a post-transcriptional inhibitor of the crvA mRNA. Mutation of vadR increases cell curvature, whereas overexpression has the inverse effect. We show that vadR transcription is activated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…Additionally, it is also worth mentioning that spherical H. pylori forms tend to self-aggregate and create biofilms [ 72 , 85 ], so it is difficult to distinguish planktonic and biofilm forms of this bacterium. According to the authors of this review, it seems that the processes of morphological transformation and biofilm formation of H. pylori are closely related and may induce one another, as observed in other microorganisms [ 86 , 87 , 88 , 89 ]. Spherical forms may stimulate biofilm formation through a high autoaggregation capacity, while biofilm may intensify the transition of H. pylori to spherical forms through the presence of niches with suboptimal growth conditions (e.g., reduced concentrations of nutrients or respiratory gases).…”
Section: Phenotypic Variability As a Modulator Of H Pylmentioning
confidence: 99%
“…Additionally, it is also worth mentioning that spherical H. pylori forms tend to self-aggregate and create biofilms [ 72 , 85 ], so it is difficult to distinguish planktonic and biofilm forms of this bacterium. According to the authors of this review, it seems that the processes of morphological transformation and biofilm formation of H. pylori are closely related and may induce one another, as observed in other microorganisms [ 86 , 87 , 88 , 89 ]. Spherical forms may stimulate biofilm formation through a high autoaggregation capacity, while biofilm may intensify the transition of H. pylori to spherical forms through the presence of niches with suboptimal growth conditions (e.g., reduced concentrations of nutrients or respiratory gases).…”
Section: Phenotypic Variability As a Modulator Of H Pylmentioning
confidence: 99%
“…VxrAB (also known as WigKR) was first identified for its implication in colonization in the infant mouse model and T6SS regulation (34). VxrAB has already been described to regulate other systems implicated in antimicrobial resistance, such as biofilm formation, motility and cell shape maintenance and homeostasis in the presence of cell wall targeting antimicrobials (30, 66, 77). In the later, they demonstrated that the expression of vxrAB is increased by antibiotic-induced cell wall damage, and that VxrAB regulates the entire cell wall synthesis pathway, leading to V. cholerae’s tolerance to antibiotics (66).…”
Section: Discussionmentioning
confidence: 99%
“…This form of regulation promotes the degradation of dsRNA by the action of RNase III (a dsRNA-specific endonuclease) and the production of small dsRNAs [ 130 ], or by blocking or inducing translation [ 131 ]. This kind of RNA regulation controls a wide range of activities inside cells, such as riboswitch elements, toxin–antitoxin modules, mobility, DNA repair, metabolism, gene regulation, cell shape, and biofilm formation [ 101 , 123 125 , 129 , 132 ]. It is also used by plasmids, TEs, and phages for self-regulation [ 100 , 101 , 128 ].…”
Section: Introductionmentioning
confidence: 99%